2006
DOI: 10.1021/ja057165y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Hydrogenation of Bis(imino)pyridine Iron Imides

Abstract: Treatment of the iron bis(dinitrogen) complex, (iPrPDI)Fe(N2)2 (iPrPDI = (2,6-iPr2C6H3N=CMe)2C5H3N), with a series of aryl azides resulted in loss of 3 equiv of N2 and formation of the corresponding four-coordinate iron imide compounds, (iPrPDI)Fe(NAr). These complexes, two of which (Ar = 2,6-iPr2-C6H3 and 2,4,6-Me3-C6H2) have been characterized by X-ray diffraction, are significantly distorted from planarity. The metrical parameters in combination with Mössbauer spectroscopic and SQUID magnetic data suggest a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
184
1
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(199 citation statements)
references
References 31 publications
10
184
1
4
Order By: Relevance
“…Furthermore, isolated nitrenes of late transition metals such as Fe, 7,8 Co, 8 and Ni 6,29 are known to transfer NR to CO to yield isocyanates. Given their importance and experimental scarcity, we undertook a proactive investigation of the bonding in copper nitrene complexes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, isolated nitrenes of late transition metals such as Fe, 7,8 Co, 8 and Ni 6,29 are known to transfer NR to CO to yield isocyanates. Given their importance and experimental scarcity, we undertook a proactive investigation of the bonding in copper nitrene complexes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Mindiola and Hillhouse have reacted a bis-(phosphine)nickel nitrene with CO to form ArNCO. 6 Bart et al 7 and Peters et al 8 have reported nitrene group transfer from structurally characterized late-transition-metal nitrene complexes (iron and cobalt, respectively) to CO to yield ArNCO. There is considerable interest in phosgene-free processes for the production of isocyanates from nitroaromatics (nitrenes are proposed as intermediates) using latetransition-metal catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have involved the reduction of 5 or 6 in the presence of nitrogen as a means of generating dinitrogen-containing complexes [53,132,133,134] .…”
Section: Well-defined Iron and Cobalt Alkylsmentioning
confidence: 99%
“…It should be noted that, as with the free ligands, the bound ligand in 1 and 2 can be the site for a range of chemistries including deprotonation (see Chapter 4 and [135,144]) . In addition several studies have involved the reduction of 1 or 2 in the presence of nitrogen as a means of generating dinitrogen -containing complexes (see Chapter 4 and [53,[145][146][147][148]) . …”
Section: Well -Defi Ned Iron and Cobalt Alkylsmentioning
confidence: 99%